2021
DOI: 10.1139/apnm-2021-0316
|View full text |Cite
|
Sign up to set email alerts
|

Increased carbohydrate availability effects energy and nutrient periodisation of professional male athletes from the Australian Football League

Abstract: This research aims to explore the effect of increased carbohydrate availability intervention on energy intake and distribution in professional Australian Football athletes. Six 24-h energy and macronutrient intakes were quantified (n= 19 males; age 24 ±4 y, stature 187 ±8 cm, mass 87 ±9 kg) using photographic food diaries and Foodworks analyses. Energy expenditure was estimated for the same period using GeneActiv accelerometers. During three control days, athletes had ad libitum access to food, while the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Since the AFLW competition is still in its infancy, it is likely that increases in match volume will be evident as the physical capabilities of players improve over future seasons, 2,5 emphasising the need to continue monitoring athletes training and match volumes and respective dietary intakes. Only a handful of studies have assessed distance covered, or other forms of training or match volume, alongside dietary intake of Australian football athletes 9,17,21 . One study reported that athletes adjusted their carbohydrate intake in accordance with physical load (total distance, average speed, and distance covered within four specific velocity bands) on match days, 17 whereas the others showed inability to match intake with training demands, 9,21 consistent with studies conducted in other team sports 23,32 …”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Since the AFLW competition is still in its infancy, it is likely that increases in match volume will be evident as the physical capabilities of players improve over future seasons, 2,5 emphasising the need to continue monitoring athletes training and match volumes and respective dietary intakes. Only a handful of studies have assessed distance covered, or other forms of training or match volume, alongside dietary intake of Australian football athletes 9,17,21 . One study reported that athletes adjusted their carbohydrate intake in accordance with physical load (total distance, average speed, and distance covered within four specific velocity bands) on match days, 17 whereas the others showed inability to match intake with training demands, 9,21 consistent with studies conducted in other team sports 23,32 …”
Section: Discussionmentioning
confidence: 76%
“…Only a handful of studies have assessed distance covered, or other forms of training or match volume, alongside dietary intake of Australian football athletes 9,17,21 . One study reported that athletes adjusted their carbohydrate intake in accordance with physical load (total distance, average speed, and distance covered within four specific velocity bands) on match days, 17 whereas the others showed inability to match intake with training demands, 9,21 consistent with studies conducted in other team sports 23,32 …”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The goal of studying athletes' energy expenditure is to gain insight into the relationship between the amount of energy used during various activities and the subsequent effects on performance and recuperation. Wearable devices or metabolic carts are two examples of innovative methods for measuring energy expenditure that could be explored in the future, together with studies examining the effects of varying training loads on energy expenditure in different populations, such as elite athletes, recreational athletes, and special populations [39,40].…”
Section: Novel Frontiers Clustersmentioning
confidence: 99%